O sindicato na mira da legislação neoliberal: impacto das leis entre o impeachment e a pré-pandemia - Victor Sousa Barros Marcial e Fraga (2022)
A new chapter in the troubled relationship between the brazilian State and unions began with the coup that caused the fall of President Dilma Rousseff in 2016. The government of her vicepresident and successor was marked by antiunion and antiworkers legislation, a feature also present in the first year of government of the president elected in 2018. The period, peculiar due to the amount of dismantling rules, can be defined as the return of defenders of orthodox neoliberalism to power in the country. The present work aims to analyze the relationship between the Brazilian State, trade unions, enterprises and neoliberalism, in historical and legislative terms, in order to demonstrate state action, together with capital, for the application of neoliberal logic in infraconstitutional legislation. The preceding theoretical and historical panorama makes it possible to verify the impact of the rules between 2016 and 2019 on the ability of unions to act and represent, either directly by frontal attacks or indirectly by the evergrowing precariousness of the labor sphere. The analysis of legislation, of explanatory statements and other governmental statements, of theoretical works specific to each theme and of doctrinal texts on the interaction between them is the methodology adopted to answer the question about how the legislative changes of the chosen period deepened the limitation of union action on behalf of the working class. The preliminary answer, confirmed by the research, is that unions were strangled in their capacity to act, with an attack on their representation responsibilities, and in their financial capacity, with the removal of only one of the pillars that subject unionism to State control. More than the expected response, however, the historical analysis of the relationship between unions, State, companies and neoliberalism revealed a continuous process – albeit in varying degrees of intensity – of castration of the collective action of workers, regardless of the political model or the system of accumulation adopted.